ISLAMIC BIOETHICAL CONCEPT OF URBANIZATION AND THE ENVIRONMENT - Javadli, G.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Many religious leaders, including Muslim theologians, associate the causes of environmental problems with the violation of divine laws and believe that the more society moves away from the Creator's values, the more devastating they approach global catastrophes. Today, ongoing historical processes and common sense prove the undeniable logical connection between global problems and God's providence. The world needs new ideological and humanitarian concepts, which can always be found in the scientific foundations of Islam and reasonably used to preserve the environment and solve the problems of urbanization. It is known that religion, as a social institution, also underwent great changes over the period of its development. It is known that in its fundamental attitudes it determines the ideological positions of believers, on the basis of which their relations with religious institutions and with other people are built. It can be said that in the overwhelming majority of cases (at least in the last hundred years) religious institutions solved problems of a moral, rather than ideological, plan. This is its vitality. Philosophy possessed such capabilities, perhaps, only in ancient Greece and perhaps in those regimes where some of its installations were elevated to the level of state ideology (legism in ancient China, Maoism - in China in the first half of the 20th century: Marxism - in the Soviet Union, and so on. .d.) Although religious ideas are conveyed to the majority of people through the "elect", i.e. the prophets, materialized in language graphics, various sacral symbolism, they then begin to actively interact with various areas of social practice. A phased analysis of the history of the development of religious ideas based on belief in the supernatural, shows that socio-anthropomorphism, in general deification of both living and inanimate nature, was characteristic of human nature. However, over time, attitudes toward nature became clearly of a socio-ecological nature.